Pengendalian Kualitas Produk Kemasan Dengan Metode Statistical Quality Control Dan Failure Mode And Effect Analysis (PT. Temprina Media Grafika) - Mochammad Daffa Amanullah; Enny Aryanny (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2023)
Temprina Media Grafika is a manufacturing company with printing and packaging services. The products are produced from PT. Temprina Media Grafika are packaging paper for various industrial products. However, the production of PT. Temprina Media Grafika still has a few problems that impact the product flaw. The purpose of this study is to identify the quality of Choco Wafer Roll packaging and offer improvements to improving the Choco Wafer Roll packaged products in PT. Temprina Media Grafika. The study was used are Statistical Quality Control (SQC) and Failure Mode and Effect Analysis (FMEA). Based on the results of research on Statistical Quality Control (SQC), the most dominant defects were color not appropriate (27,2%), after that shiny color not right (23,4%), uneven colors (21,9%), Spots appear on the pack (15,3%), and packaging design cut (12,3%). Based on the results of research on Failure Mode and Effect Analysis (FMEA), it is known that the problem causing disability with the highest RPN value of 168 is the machine factor with the cause of dirty UV polymer containers. Recommendations for improvements that can be made are Eliminating uv polymer containers after uv laminate processes.